Software Engineering and Algorithms in Intelligent Systems Proceedings of 7th Computer Science On-line Conference 2018, Volume 1 - Silhavy, Radek (Advances in Intelligent Systems and Computing, 2019)
This book presents new software engineering approaches and methods, discussing real-world problems and exploratory research that describes novel approaches, modern design techniques, hybrid algorithms and empirical methods. This book constitutes part of the refereed proceedings of the Software Engineering and Algorithms in Intelligent Systems Section of the 7th Computer Science On-line Conference 2018 (CSOC 2018), held in April 2018.